Dynamics of Patrilineal Inheritance System Change in Urban Lampung Indigenous Community in Bandar Lampung City - Muslim, Muslim; Kurniati, Herlina; Abror, Khoirul (Analisis: Jurnal Studi Keislaman, 2024)
Lampung customary inheritance system generally applies a pure patrilineal system, where sons become heirs from the father's side, while daughters have no position as heirs. However, along with the times, there have been changes in the implementation of inheritance in urban Lampung customary society, especially in Bandar Lampung City. The dynamics of this change are influenced by various factors, one of which is the increasingly common occurrence of mixed marriages. Therefore, this study aims to examine the dynamics of changes in the inheritance system by considering the various factors that influence it. This research uses a qualitative approach with a type of empirical juridical research that is analytically descriptive. Data were obtained through interviews as primary data and document analysis as secondary data. Data processing is done through the stages of data reduction, data presentation, and conclusion drawing. The results showed that the dynamics of change in the patrilineal inheritance system in Lampung customary society in Bandar Lampung City reflected a paradigm shift that occurred gradually in response to the influence of external and internal factors, such as the environment, educational development, religious influence, and others. Although the patrilineal inheritance system is still influential, these changes lead to a fairer and more equitable distribution of inheritance, while still maintaining existing religious and customary principles, as well as respecting the philosophy of life of the Lampung people.